Strain Distribution Formability in Shallow Parts - Waddington, Ernest (My University, 1980)
In shallow parts it is important to obtain strain over the face of the part if a satisfactory part is to be produced. The strain distributing formability of materials is an important parameter influencing the amount of face strain in shallow parts. Strain distributing formability is not well defined or measured.
The increased use in automobile components of high strength to weight materials such as dual phase steels requires greater precision in ranking materials for formability if these steels are to replace the conventional low strength steels.
In this work an analytical modelling technique simulating a shallow part was developed. The technique was then used to examine how various parameters (geometric, material, and friction) affect the face strain in a shallow part.
An experimental rig was designed and constructed which simulated a simple shallow part. The strains in the part were measured and used to verify the accuracy of the analytical modelling as well as give some indication of the friction conditions in a pressing operation. The experimental bottom strains are a possible means for ranking material formability in shallow pans. This ranking method and other methods based on tensile test data are discussed.
Keywords: Mechanical Engineering; Mechanical Engineering